Penerapan Model Bengkel Sastra Untuk Meningkatkan Kemampuan Mahasiswa Menulis Dan Mengapresiasi Sastra - Rohayati, Etty; Abidin, Yunus (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2010)
Abstrak Some mistake are finding in teaching and learning literature at the schools until today. This condition happened because there is some mistake in teaching and learning literature at the university. Because of that, the process of teaching and learning literature at university must be change by using the effective models of teaching and leaning which can improve student ability in appreciation and writing poetry. One of the models for teaching and learning appreciation and writing poetry at the students university is bengkel sastra model. The problems of this research are (1) how to using bengkel sastra model in teaching and learning process of appreciation and writing poetry?; and (2) how can bengkel sastra model improve student ability in appreciation and writing poetry? The aims of this research are to know (1) the using of bengkel sastra model in teaching and learning process of appreciation and writing poetry; and (2) student ability in appreciation and writing poetry by using bengkel sastra model. Method of this research is classroom action research. The subject of this research is student in Indonesia Language concentration at PGSD Department, UPI Cibiru Campus. Measurement utilizes test and observation. The trigonometry analysis technique is using to analysis the date. Result of this research concludes that (1) bengkel sastra model can improve student ability in appreciation poetry and (2) bengkel sastra model can improve student ability in writing poetry. Thus, bengkel sastra model can using to improving student ability in appreciation poetry by using reader responds approach. Bengkel sastra model can using to improving student ability in writing poetry especially in diction, imagination, sense, and rime, but cannot optimal functions to improve student ability in choosing theme, making message, tone, and felling.Key Word: bengkel sastra model, writing, appreciation poetry